A Novel Germline Mutation of KEAP1 (R483H) Associated with a Non-Toxic Multinodular Goiter - Nishihara, Eijun; Hishinuma, Akira; Kogai, Takahiko; Takada, Nami; Hirokawa, Mitsuyoshi; Fukata, Shuji; Ito, Mitsuru; Yabuta, Tomonori; Nishikawa, Mitsushige; Nakamura, Hirotoshi; Amino, Nobuyuki; Miyauchi, Akira (Frontiers in Endocrinology, 2016)
Background: A germline mutation of KEAP1 gene was reported as a novel genetic abnormality associated with familial multinodular goiter. That report was limited, and the pathogenic features were not well established. Patient Findings: We report a 47-year-old Japanese woman who presented with hyperthyroidism and a large multinodular goiter. The family history was notable for a paternal history of goiter. Graves’ disease was diagnosed based on positive TRAb, but scintiscan imaging showed that the patient’s radioiodine uptake was restricted in the non-nodular areas, indicating largely cold nodules. A total thyroidectomy was performed. The resected thyroid tissue weighed 209 g, and subsequent pathological findings were benign. The patient had a germline heterozygous KEAP1 mutation, c. 1448 G>A, resulting in an amino acid substitution (p.R483H). A next-generation sequencing analysis covering all known genes associated with multinodular goiter showed no additional germline mutation. The nuclear accumulation of NRF2, a protein associated with KEAP1, was shown at much higher rates in the patient’s nodules compared to nodules obtained from four unrelated patients with multinodular goiters. Conclusions: A novel germline mutation (R483H) of KEAP1 gene was associated with the development of a nontoxic multinodular goiter.